2017
DOI: 10.1038/ncomms14890
|View full text |Cite
|
Sign up to set email alerts
|

Iron minerals within specific microfossil morphospecies of the 1.88 Ga Gunflint Formation

Abstract: Problematic microfossils dominate the palaeontological record between the Great Oxidation Event 2.4 billion years ago (Ga) and the last Palaeoproterozoic iron formations, deposited 500–600 million years later. These fossils are often associated with iron-rich sedimentary rocks, but their affinities, metabolism, and, hence, their contributions to Earth surface oxidation and Fe deposition remain unknown. Here we show that specific microfossil populations of the 1.88 Ga Gunflint Iron Formation contain Fe-silicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 68 publications
6
77
0
Order By: Relevance
“…() reported R 3/2 values of 0.33 ± 0.09 for Bitter Springs filaments, 0.32 ± 0.10 for Bitter Springs coccoids, 0.45 ± 0.04 for aggregates of Gunflint filaments and coccoids, and 0.43 ± 0.11 for Gunflint amorphous organic matter (Figure ). Because these microfossils are morphologically interpreted as having originally been cyanobacteria (Awramik & Barghoorn, ; Barghoorn & Schopf, ; Barghoorn & Tyler, ; Lepot et al., ; Schopf, ; Schopf & Blacic, ), it is likely that they had R 3/2 values comparable to those of whole extant cyanobacterial cells (i.e., the starting materials of this study; R 3/2 = ~0.7). However, the R 3/2 values presently observed for these microfossils are smaller than those observed for the whole cells (Figure ); therefore, the R 3/2 values are inferred to have decreased during fossilization.…”
Section: Discussionmentioning
confidence: 89%
“…() reported R 3/2 values of 0.33 ± 0.09 for Bitter Springs filaments, 0.32 ± 0.10 for Bitter Springs coccoids, 0.45 ± 0.04 for aggregates of Gunflint filaments and coccoids, and 0.43 ± 0.11 for Gunflint amorphous organic matter (Figure ). Because these microfossils are morphologically interpreted as having originally been cyanobacteria (Awramik & Barghoorn, ; Barghoorn & Schopf, ; Barghoorn & Tyler, ; Lepot et al., ; Schopf, ; Schopf & Blacic, ), it is likely that they had R 3/2 values comparable to those of whole extant cyanobacterial cells (i.e., the starting materials of this study; R 3/2 = ~0.7). However, the R 3/2 values presently observed for these microfossils are smaller than those observed for the whole cells (Figure ); therefore, the R 3/2 values are inferred to have decreased during fossilization.…”
Section: Discussionmentioning
confidence: 89%
“…However, Awramik (1976) noted that the distinctions between the three species may vary due to abiotic factors, such as mineral precipitation or cell degradation during diagenesis. Similarly, Lepot et al (2017) found that at the nanoscale, variation in cell wall thickness was correlated with quartz crystal distribution and cell diameter, noting an apparent true difference between thin-walled and thick-walled Huroniospora varieties. Similarly, Lepot et al (2017) found that at the nanoscale, variation in cell wall thickness was correlated with quartz crystal distribution and cell diameter, noting an apparent true difference between thin-walled and thick-walled Huroniospora varieties.…”
Section: Comparison With Gunflint Iron Formation Microfossilsmentioning
confidence: 85%
“…1.88 Ga IFs in the Animikie Basin of the Lake Superior region (e.g., Tyler and Barhoorn, 1954;Barghoorn and Tyler, 1965;Cloud, 1965). Based on the assumption that the microfossils were cyanobacteria, or their predecessors, Cloud (1973) Formation appear to confirm that cyanobacteria were a significant component of shallow-marine communities at that time (Lepot et al, 2017). What makes this model particularly intriguing, however, is experimental work demonstrating that Fe(II) concentrations in the range of 10s to 100s…”
mentioning
confidence: 94%
“…These contradictory findings may suggest that primitive cyanobacteria had, at least by 1.9 Ga, some form of protection mechanism against Fe(II) concentrations becoming too high in proximal environments. In this regard, the study of Lepot et al (2017) oxidation at circumneutral pH are slow under microaerobic conditions (e.g., Søgaard et al, 2000).…”
mentioning
confidence: 99%